Cocaine- and opiate-related fatal overdose in New York City, 1990-2000 - Tardiff Ken; Gross Charles; Piper Tinka; Bucciarelli Angela; Bernstein Kyle T; Galea Sandro (BMC, 2007)
Abstract Background In New York City (NYC), the annual mortality rate is higher for accidental drug overdoses than for homicides; cocaine and opiates are the drugs most frequently associated with drug overdose deaths. We assessed trends and correlates of cocaine- and opiate-related overdose deaths in NYC during 1990-2000. Methods Data were collected from the NYC Office of the Chief Medical Examiner (OCME) on all fatal drug overdoses involving cocaine and/or opiates that occurred between 1990-2000 (n = 8,774) and classified into three mutually exclusive groups (cocaine only; opiates-only; cocaine and opiates). Risk factors for accidental overdose were examined in the three groups and compared using multinomial logistic regression. Results Overall, among decedents ages 15-64, 2,392 (27.3%) were attributed to cocaine only and 2,825 (32.2%) were attributed to opiates-only. During the interval studied, the percentage of drug overdose deaths attributed to cocaine only fell from 29.2% to 23.6% while the percentage of overdose deaths attributed to opiates-only rose from 30.6% to 40.1%. Compared to New Yorkers who fatally overdosed from opiates-only, fatal overdose attributed to cocaine-only was associated with being male (OR = 0.71, 95% CI 0.62-0.82), Black (OR = 4.73, 95% CI 4.08-5.49) or Hispanic (OR = 1.51, 95% CI 1.29-1.76), an overdose outside of a residence or building (OR = 1.34, 95% CI 1.06-1.68), having alcohol detected at autopsy (OR = 0.50, 95% CI 0.44-0.56) and older age (55-64) (OR = 2.53 95% CI 1.70-3.75)). Conclusion As interventions to prevent fatal overdose become more targeted and drug specific, understanding the different populations at risk for different drug-related overdoses will become more critical.